2022
DOI: 10.3390/ph15091070
|View full text |Cite
|
Sign up to set email alerts
|

Farnesiferol C Exerts Antiproliferative Effects on Hepatocellular Carcinoma HepG2 Cells by Instigating ROS-Dependent Apoptotic Pathway

Abstract: Farnesiferol C (Far-C) is a coumarin commonly extracted from Ferula asafetida and is popularly used as a traditional source of natural remedy. Liver cancer or hepatocellular carcinoma (HCC) has emerged as a major cause behind cancer burden, and limited therapeutic interventions have further aggravated the clinical management of HCC. In the present study, the authors tested the hypothesis that Far-C-instigated oxidative stress resulted in anti-proliferation and apoptosis instigation within human liver cancer He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In this study, we focused on the suppression of SW480 cell treated with plantaricin BM-1 via induction of apoptosis. In previous studies, Hoechst33342 staining was used to observe the increase in fluorescence intensity of apoptotic cells, as well as aggregation and fragmentation of the nuclei ( Goud et al, 2020 ; Wu et al, 2020 ; Huang et al, 2021 ; Alafnan et al, 2022 ). This was similar to our results ( Figure 3 ) using Hoechst33342 staining, which demonstrated that after receiving plantaricin BM-1 for 1 h, the initiation of the apoptosis process via enhanced chromatin condensation and the number of cells with condensed nuclei of high fluorescence intensity was increased dose-dependently.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the suppression of SW480 cell treated with plantaricin BM-1 via induction of apoptosis. In previous studies, Hoechst33342 staining was used to observe the increase in fluorescence intensity of apoptotic cells, as well as aggregation and fragmentation of the nuclei ( Goud et al, 2020 ; Wu et al, 2020 ; Huang et al, 2021 ; Alafnan et al, 2022 ). This was similar to our results ( Figure 3 ) using Hoechst33342 staining, which demonstrated that after receiving plantaricin BM-1 for 1 h, the initiation of the apoptosis process via enhanced chromatin condensation and the number of cells with condensed nuclei of high fluorescence intensity was increased dose-dependently.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of apoptosis within HCT116 cells, upon exposure with 5‐FU‐loaded exosomes, was evaluated using acridine orange and ethidium bromide dual staining (Alafnan et al, 2022). In brief, 5 × 10 5 HCT116 cells were subjected to 5‐FU‐loaded exosomes (equivalent to 2.5 μg and 5 μg 5‐FU) for 24 h. Thereafter, the cells were stained with a mixture of AO/EtBr stain (10 μl each) and were incubated in the dark for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of 5‐FU‐loaded exosomes on ΔΨm in HCT116 cells was estimated using Rh123 (Alafnan et al, 2022). Approximately 2 × 10 5 HCT116 cells were seeded in each well of a 96‐well plate and left overnight in humidified atmosphere at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations